He Representation Of Id, Ego And Superego In Sylvia Plath’S Selected Poems: “A Literary Psychological Approach” - Akso, Al; Efendi, Dedi; Oktariza, Dodi (Universitas Muara Bungo, 2025)
This study explains the representation of the id, ego, and superego in selected poems by Sylvia Plath through a literary psychology approach, particularly based on Sigmund Freud's psychoanalytic theory. The purpose of this study is to describe how Plath's inner conflict and psychological turmoil are reflected in her poems, as well as to reveal the messages conveyed through the representation of the id, ego, and superego in the selected poems of Sylvia Plath. The researcher uses a descriptive qualitative method by selecting three poems from The Collected Poems anthology, edited by Ted Hughes: